The oral bacterial microbiome of occlusal surfaces in children and its association with diet and caries - Ribeiro, Apoena Aguiar; Azcarate-Peril, Maria Andrea; Cadenas, Maria Belen; Butz, Natasha; Paster, Bruce J.; Chen, Tsute; Bair, Eric; Arnold, Roland R. (PloS one, 2017)
Dental caries is the most prevalent disease in humans globally. Efforts to control it have been invigorated by an increasing knowledge of the oral microbiome composition. This study aimed to evaluate the bacterial diversity in occlusal biofilms and its relationship with clinical surface diagnosis and dietary habits. Anamneses were recorded from thirteen 12-year-old children. Biofilm samples collected from occlusal surfaces of 46 permanent second molars were analyzed by 16S rRNA amplicon sequencing combined with the BLASTN-based search algorithm for species identification. The overall mean decayed, missing and filled surfaces modified index [DMFSm Index, including active white spot lesions (AWSL)] value was 8.77±7.47. Biofilm communities were highly polymicrobial collectively, representing 10 bacterial phyla, 25 classes, 29 orders, 58 families, 107 genera, 723 species. Streptococcus sp_Oral_Taxon_065, Corynebacterium matruchotii, Actinomyces viscosus, Actinomyces sp_Oral_Taxon_175, Actinomyces sp_Oral_Taxon_178, Actinomyces sp_Oral_Taxon_877, Prevotella nigrescens, Dialister micraerophilus, Eubacterium_XI G 1 infirmum were more abundant among surfaces with AWSL, and Streptococcus gordonii, Streptococcus sp._Oral_Taxon_058, Enterobacter sp._str._638 Streptococcus australis, Yersinia mollaretii, Enterobacter cloacae, Streptococcus sp._Oral_Taxon_71, Streptococcus sp._Oral_Taxon_F11, Centipeda sp._Oral_Taxon_D18 were more abundant among sound surfaces. Streptococcus mutans was detected on all surfaces in all patients, while Streptococcus sobrinus was detected only in three patients (mean relative abundances 7.1% and 0.6%, respectively). Neither species differentiated healthy from diseased sites. Diets of nine of the subjects were scored as high in fermentable carbohydrates (≧2X/day between meals). A direct association between relative abundances of bacteria and carbohydrate consumption was observed among 18 species. High consumption of fermentable carbohydrates and sound surfaces were associated with a reduction in bacterial diversity. PCoA plots displayed differences in bacterial community profiles between sound and diseased surfaces. Our study showed that, in addition to mutans streptococci, other species may be associated with the initiation of dental caries on occlusal surfaces, and that biofilm diversity of tooth surfaces is influenced by carbohydrate consumption and a surface's health status.